Acute pancreatitis; etiopathogenetic and clinical research - İrfan SOYKAN and Abdülkadir DÖKMECİ and Hülya ÇETİNKAYA and Ali Reşit Beyler and Necati ÖRMECİ and; et BAŞTEMİR and Ramazan IDILMAN and Kadir BAHAR and Selim KARAYALÇIN and Cihan YURDAYDIN and et al. (Turkish Journal of Gastroenterology, 2020)
-